The EFL textbook and ideology: an analysis of the characters included in two global EFL textbooks - Vagni Jajam, Ana Gabriela (2021)
Fil: Vagni Jajam, Ana Gabriela. Universidad Nacional del Litoral. Facultad de Humanidades y Ciencias; Argentina.